Incidence of salivary side effects after radioiodine treatment using a new specifically-designed questionnaire. Issue 6 (July 2017) - Moreddu, E.; Baumstarck-Barrau, K.; Gabriel, S.; Fakhry, N.; Sebag, F.; Mundler, O.; Chossegros, C.; Taïeb, D.
Abstract: Sialadenitis is one of the common complications of radioiodine treatment for thyroid malignancy. The aim of this study was to evaluate the prevalence of radioiodine-induced sialadenitis and other side effects by using a self-administered questionnaire. From 1 January 2011 to 31 December 2012 all consecutive patients with a newly-established diagnosis of thyroid cancer who were treated with adjuvant radioiodine at La Timone University Hospital were sent a self-administered questionnaire on salivary complaints that had been specifically designed for this study. A total of 413 patients sent the questionnaire back, of whom 100 (24%) had experienced pain, 116 (28%) discomfort or swelling, and 147 (36%) dry mouth or xerostomia. This survey has highlighted the number of side effects of radioiodine treatment in a large group of patients and corroborates previous observations. Our new self-administered questionnaire may be useful to others for follow-up and research.